Digital Atmosphere dan Loyalitas Konsumen: Bukti dari Kota Santri - Nissa Sayyidah Fatwa; Harmon Chaniago (Politeknik Negeri Batam, 2022)
One of the biggest digital adoptions in marketing is the emergence of marketplaces. Several marketplaces are operating in Indonesia, including Tokopedia. Tokopedia has collaborated with the government to develop traditional markets and to encourage MSMEs in the student city of Tasikmalaya (Tasikmalaya city and district). Tokopedia has the highest number of visitors, but it is below its competitors in purchase transactions. The main reason is the high bounce rate; consumers look at the application for a while, then exit again. Theoretically, this problem is known as digital atmosphere. We conducted two pre-surveys to ensure that there were problems. This study investigates these problems and relates them to consumer loyalty. The research was carried out from February 2022 – May 2022 using quantitative descriptive methods. The data were collected using an online questionnaire (G-form) and social media assistance. The total sample is 190 respondents. Analysis of the data using the average test and regression. The results of the study conclude that the digital atmosphere has a positive effect on consumer loyalty. This research also proves that improving the digital atmosphere in the marketplace on an ongoing basis will increase the number of consumers and sales transactions of shops selling within the marketplace. For marketplace managers who want to increase the number of visitors and real transactions from consumers, using the indicators listed in the article's contents is highly recommended. This research needs to be continued for other cities in Indonesia and developed from the perspective of entrepreneurs.